Chemosystematically valuable triterpenoid saponins from Glandularia x hybrida. (July 2020) - Mohamed, Nesma M.; Makboul, Makboul A.; Farag, Salwa F.; Wang, Yan-Hong; Mohamed, Shaymaa M.; Ross, Samir A.
Abstract: Phytochemical investigation of the ethanolic extract of Glandularia x hybrida roots resulted in the isolation and identification of five previously undescribed saponins, 3- O - β -ᴅ-xylopyranosyl-hederagenin-28- O - β -ᴅ-glucopyranosyl (1→2)- O - β -ᴅ-glucopyranosyl ester, 3- O - β -ᴅ-xylopyranosyl-hederagenin-28- O - β -ᴅ-glucopyranosyl (1→2)-[ β -ᴅ-glucopyranosyl (1→6)]- β -ᴅ-glucopyranosyl ester, hederagenin-28- O - β -ᴅ-glucopyranosyl (1→2)-[ β -ᴅ-glucopyranosyl (1→6)]- β -ᴅ-glucopyranosyl ester, 23- O -acetyl-3- O - β -ᴅ-xylopyranosyl-pomolic acid-28- O - β -ᴅ-glucopyranosyl ester, and 23- O -acetyl-pomolic acid-3- O - β -ᴅ-xylopyranoside, along with eleven structurally diverse compounds. The structural characterizations of the isolated compounds were determined using physical data, comprehensive 1D and 2D NMR spectral analysis, and HRESIMS. All isolated saponins are hederagenin or pomolic acid glycosides conjugated with differentiable sugar units bound to C-3 and/or C-28 of the aglycone through ether and/or ester glycosidic linkages, respectively. Structural diversity of these isolated secondary metabolites would have a great impact on the future chemosystematic studies of this plant. Four saponins, obtained in good yield were evaluated for their anti-inflammatory activities in a rat model using the carrageenan-induced paw edema protocol. Two of these exhibited significant anti-inflammatory activities demonstrated through inhibition of the paw edema by 64 and 60%. Graphical abstract: Image 1 Highlights: Chemical profile of Glandularia x hybrida was investigated for the first time. Five triterpenoid saponins were described for the first time from nature. Distinguishing chemosystematic features between the two closely related genera ( Glandularia and Verbena ) were established. Two compounds showed anti-inflammatory activities with significant reduction of edema..